Bioinsecticide textile bags for control of maize weevil during grain storage - Peschiutta, María Laura; Brito, Vanessa Daniela; Krapacher, Claudio Ricardo; Achimón, Fernanda; Pizzolitto, Romina Paola; Santa Juliana, Diego Mauricio; Zunino, María Paula (Elsevier, 2025)
The loss of stored grains due to the activity of insects is one of the main problems in maize production. The maize weevil, Sitophilus zeamais, is one of the major pests found in storage systems. We developed and evaluated the insecticidal efficiency against S. zeamais of three different bioactive fabric bags (cotton, polypropylene, and fibranne) loaded with latex paint-based formulation and pulegone, alpha-methly-trans-cinnamaldehyde, and a mixture of both compounds (at 24 and 48 h of exposure). Additionally, we determined the phytotoxicity of these formulations on maize grains and the release from the bags of the formulation with pulegone, that is, the amount of pulegone that is emitted from the bags. We found that at 24 h of exposure pulegone (1%) fibranne and cotton bags (26.71% and 15.81% respectively) were more effective against weevils than pulegone (1%) polypropylene (5.34%). The bags painted with the pulegone formulation at higher concentrations (at 2% and 3%) were effective, regardless of the fabric type used (cotton, polypropylene, or fibranne fabrics). The formulations with pulegone were not phytotoxic. Moreover, cotton bags showed the highest release of pulegone. These results are of interest because cotton bags painted with formulations based on pulegone-paint could serve as a potential tool for controlling the maize weevil in a grain storage system, such as in small storage in sacks or silo-bags.